Spatiotemporal variability of a stadium football pitch during a professional tournament - Burbrink, C. M.; Straw, C. M. (Sports Engineering, 2023)
Natural turfgrass football pitches are variable across a competitive season. However, short-term variability has not been explored to the same extent, specifically in stadium environments during tournaments. Pitch maintenance and recovery time between matches during tournaments are inherently reduced and may increase spatiotemporal variability of surface characteristics. Therefore, the purpose of this technical note was to present a unique case study investigating short-term variability of surface characteristics within a stadium pitch during a seven-game, 9-day tournament. The study was conducted in December 2020 at a stadium in central Florida during a professional football tournament. The pitch consisted of `Latitude 36` hybrid bermudagrass [Cynodon dactylon L. (Pers.) × C. transvaalensis Burtt-Davy] on a sand rootzone. It was tested daily throughout the tournament at 100 locations using various testing devices that measured surface hardness (Gmax), soil moisture (% volumetric water content), turfgrass cover (0-100%), and normalized difference vegetation index (NDVI; 0-1). Data were analyzed to evaluate the spatial, temporal, and spatiotemporal variability of each surface characteristic. Surface hardness and soil moisture were found to change the least, while turfgrass cover changed the most. Routine, targeted management applications were suggested to alleviate preexisting surface hardness and soil moisture variability, and intently monitoring foot traffic patterns was suggested to aide in more uniform turfgrass cover and normalized difference vegetation index during a tournament. Additional research is needed that explores other stadium scenarios, with the goal of developing data-driven management approaches that assist in providing the most consistent pitch possible in stadiums during professional tournaments.